2015
DOI: 10.22146/ijc.21200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fe Ionic-Imprinted Polyeugenol Using Polyethylene Glycol Diglycidilether as Cross-Linking Agent for Sorption of Fe(III)

Abstract: Fe-Ionic Imprinted Polymer (IIP) from polyeugenol as base polymer and polyethylene glycol diglycidyl ether (PEGDE) as cross-linking agent had been synthesized to adsorb Fe(III) from aqueous media. The non-imprinting material (NIP) and polyeugenol were used in the adsorption study as control. Synthesis work included polymerization, template uploading, crosslinking and template removal, optimized for different template ion upload pH and concentrations. The polymers were characterized by FTIR spectroscopy, XRD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…PEGDE is applied as a crosslinking agent as well as a plasticizer, which will increase the mechanical strength of the membrane. Based on previous studies, PEGDE crosslinked PVA based membranes have been shown to have good mechanical strength as indicated by the results of tensile strength tests [15][16].…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PEGDE is applied as a crosslinking agent as well as a plasticizer, which will increase the mechanical strength of the membrane. Based on previous studies, PEGDE crosslinked PVA based membranes have been shown to have good mechanical strength as indicated by the results of tensile strength tests [15][16].…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…The crosslink reaction in the IIM manufacturing process here, in addition to adding polymer chains and increasing the mechanical strength of the membrane, also plays a role in locking the Au 3+ metal ion template on the PEATM polymer, so that an appropriate imprint will be formed [16]. Fig.…”
Section: Characterization Of Iim Ftirmentioning
confidence: 99%
“…IIP 3 mol menghasilkan luas area 0,00 m 2 /g kemungkinan dikarenakan polimer yang mengalami shrinkage (penyusutan) yang mengakibatkan luas permukaannya sangat kecil. Penurunan luas permukaan ini dialami oleh peneliti lain diantaranya Buhani et al (2010), Djunaidi et al (2015), dan lain-lain.…”
Section: Analisis Betunclassified
“…The content of eugenol in cloves ranges from 60-90% (Sneddon, 1997). Eugenol is an Indonesian natural ingredient that can be used for the separation of metal ions (Djunaidi, Jumina, Siswanta, & Ulbricht, 2015;. Eugenol is used as a starting material for the synthesis of a compound because there are three functional groups that are bound to it, namely the allyl, hydroxyl and methoxy groups that can potentially work as functional monomers for the selective adsorption process of Cu (Djunaidi, Wibawa, & Murti, 2018).…”
Section: Introductionmentioning
confidence: 99%